Paradigm Shift in a Multilinguistic Context: Constructing National Identity and Socio-Religious Harmony in Cameroon Urban Music - Fai, Gilbert Tarka; Vernyuy, Lawir Blessing (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2025)
Cameroon, often described as "Africa in miniature," possesses a complex social fabric defined by over 250 ethnic groups and a dual colonial heritage of English and French. In this fragmented landscape, constructing a unified national identity has historically been challenged by linguistic and religious cleavages. This research explores the paradigm shift in Cameroon urban music, where the emergence of Franc-Anglais (Camfranglais) serves as a vehicle for national integration and socio-religious harmony. Using a qualitative sociolinguistic approach and the lens of multiculturalism, this study analyzes the lyrics of prominent urban artists such as Stanley Enow, Jovi, and Locko. The results indicate that while traditional genres like Makossa and Bikutsi are rooted in specific ethnic and religious identities, contemporary urban music transcends these boundaries. By blending official languages, indigenous dialects, and religious symbolism, urban music constructs a hybrid identity that resonates with the "vivre ensemble" (living together) national policy. The study concludes that urban music acts as a "secular liturgy" that facilitates inter-ethnic dialogue and promotes a collective sense of belonging amidst the ongoing Anglophone-Francophone crisis.